2009
DOI: 10.2337/dc08-2110
|View full text |Cite
|
Sign up to set email alerts
|

Ranirestat for the Management of Diabetic Sensorimotor Polyneuropathy

Abstract: OBJECTIVEAldose reductase inhibitors (ARIs) are potential disease modifiers for diabetes complications. We aimed to determine whether ranirestat, an ARI, could slow or reverse the course of diabetic sensorimotor polyneuropathy (DSP).RESEARCH DESIGN AND METHODSA total of 549 patients with DSP were randomly assigned to treatment with placebo or 10, 20, or 40 mg/day ranirestat for 52 weeks in this multicenter, double-blind study. Efficacy was evaluated by nerve conduction studies, the modified Toronto Clinical Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 17 publications
1
75
0
5
Order By: Relevance
“…The natural progression of DPN would be expected to result in a slowing of SNCV i by ;0.6-0.7 m/s after 12 months (25,26). Nevertheless, several clinical trials in patients with diabetic neuropathy have reported increases in SNCV i in the placebo group of a similar or somewhat smaller magnitude (14,27,28) than that observed in the current study.…”
Section: Discussionsupporting
confidence: 68%
“…The natural progression of DPN would be expected to result in a slowing of SNCV i by ;0.6-0.7 m/s after 12 months (25,26). Nevertheless, several clinical trials in patients with diabetic neuropathy have reported increases in SNCV i in the placebo group of a similar or somewhat smaller magnitude (14,27,28) than that observed in the current study.…”
Section: Discussionsupporting
confidence: 68%
“…In patients with diabetes treated with ranirestat for 12 weeks, the drug dose dependently inhibited sorbitol and fructose levels in the sural nerve (Bril and Buchanan, 2004), and a 48-week extension of this study revealed an improvement in SNCV by Ն1 m/s relative to baseline and compared with placebo (Bril and Buchanan, 2006). Unfortunately, in phase 3 testing, 52 weeks of ranirestat treatment (20 and 40 mg/day) failed to improve summed SNCV, possibly related to an unexpected improvement in SNCV in the placebo group (Bril et al, 2009). However significant improvements in MNCV were observed and the drug was well tolerated, suggesting that a more refined trial design may demonstrate efficacy in the primary endpoint of summed SNCV (Bril et al, 2009).…”
Section: B Targeting Casual Mechanismsmentioning
confidence: 93%
“…Unfortunately, in phase 3 testing, 52 weeks of ranirestat treatment (20 and 40 mg/day) failed to improve summed SNCV, possibly related to an unexpected improvement in SNCV in the placebo group (Bril et al, 2009). However significant improvements in MNCV were observed and the drug was well tolerated, suggesting that a more refined trial design may demonstrate efficacy in the primary endpoint of summed SNCV (Bril et al, 2009).…”
Section: B Targeting Casual Mechanismsmentioning
confidence: 99%
“…However, it failed to show a statistically significant difference in sensory nerve function relative to placebo. Ranirestat was well tolerated with no pertinent differences in drug-related adverse events or in effects on clinical laboratory parameters, vital signs, or electrocardiograms among the four groups [99].…”
Section: Ranirestat (As-3201)mentioning
confidence: 99%
“…Ranirestat has been well studied by Bril and coworkers [98,99]. In a double-blind, placebocontrolled nerve biopsy trial study, 12-week-treatment with ranirestat at a dose of 5 or 20 mg/day improved nerve function in patients with diabetic sensorimotor polyneuropathy, and the improvement could be maintained.…”
Section: Ranirestat (As-3201)mentioning
confidence: 99%